Reciprocal transplant experiment suggests host specificity of the mistletoe Agelanthus natalitius in South Africa. (13th December 2013) - Okubamichael, Desale Y.; Griffiths, Megan E.; Ward, David
Abstract: We surveyed the community composition of trees that host the mistletoe Agelanthus natalitius (Loranthaceae) at two sites (Highover and Mtontwane) in South Africa. We recorded a total of 1464 trees ( Acacia karroo and A. caffra ) hosting 1202 mistletoes in the 64 surveyed plots (20 × 50 m). There were almost four times as many A. karroo as A. caffra at Highover and three times as many A. karroo as A. caffra at Mtontwane. There was no significant difference in prevalence (percentage of infected trees) at Highover ( A. karroo = 22% and A. caffra = 26%), but a significantly greater percentage of A. caffra trees were parasitized at Mtontwane ( A. karroo = 25% and A. caffra = 34%). Intensity of infection (number of mistletoe infections per tree) was higher for A. karroo (0.73 ± 0.04 and 1.03 ± 0.64) than for A. caffra (0.66 ± 0.01 and 0.89 ± 0.035) at Highover and Mtontwane, respectively. Prevalence and intensity of infection showed a significant positive relationship with tree size for both host species at both sites. We tested the genotype-by-environment interaction effects in this mistletoe by conducting reciprocal transplant experiments (64 individual trees each received 20 seeds). Initial germination was not site-, substrate- or host-sensitive. However, a general pattern was found that hypocotyls of the germinated seeds grew longer when seeds were placed on the same host species as the parent plant within their own source locality. Consistent with this observation, mistletoes placed on their source host species generally had higher survival than those transferred to non-source host species after 6 mo. Overall, mistletoe seeds from parent plants on A. karroo and mistletoe seeds placed on A. karroo had the highest survival. This could be the result of an adaptation of the mistletoe to the most frequently encountered host species.